The Development of Differentiated Learning Material for Teaching English to 6th-grade Students in Elementary School - Komang Sri Vidyartika Putri; Ni Wayan Surya Mahayanti; Putu Kerti Nitiasih (Departement of Mathematics Education, 2024)
The use of teaching materials to teach English language in the classroom is an important aspect and must be paid attention to English language teachers in classroom learning. This research aims to develop teaching materials that are varied and differentiated in activities using 3 learning methods consisting of problem-based learning, project-based learning, and discovery learning. Apart from that, the teaching materials developed are also differentiated in material content that adapts to students' learning styles, consisting of 4 learning styles: visual, aural, read/write, and kinaesthetic. In this part of developing teaching materials, researchers went through 2 comprehensive stages: design and development. The design stage consists of creating a matrix that is used as a reference in developing teaching materials, and selecting material, and the final stage is making a draft using Word. In the development stage, researchers went through stages consisting of designing a draft as well as developing media for activities, a revision process for the draft developed, finalization based on the results of revisions to the product, and assessments from experts.